PERHITUNGAN STRUKTUR RENCANA GEDUNG REKTORAT UNIVERSITAS 17 AGUSTUS 1945 SAMARINDA - AJI, HESTU PURNOMO (KURVA S JURNAL MAHASISWA, 2016)
At this time the construction of multi-storey building has become a top priority for both the private sector and government. It is very closely related to the limitations of available land and high land prices in major cities as a result of rapid population growth. The plan of University Rectoral Building of 17 Agustus 1945 in Samarinda has basic planning concept that relates directly to the knowledge in the field of civil engineering. In this thesis calculating rector building structure including with 13 basements by using the required regulations and applicable in Indonesia, such as: ISO 1727-2013 ISO 1727-2013 on Minimum Load For Designing Buildings and Other Structures, and ISO 2847-2013 on Requirements for Structural Concrete Building. From the calculation of the structure using two methods, namely Matrix and software tools SAP2000 obtained the greatest value from your bar = 96.653, Pu column = 28.751 tonnes. From the planning and calculations that have been done shows the dimensions and reinforcement of structural elements (beams, columns, plates and foundations) and plans figure of the structure of the Rectoral building.